Efficacy of Sorafenib for the Treatment of Post-Transplant Hepatocellular Carcinoma Recurrence - Kang, Seong Hee (J Korean Med Sci, 2018)
BACKGROUND: The role of sorafenib in patients with hepatocellular carcinoma (HCC) recurrence after liver transplantation (LT) has been rarely studied. The aim of this study was to evaluate the efficacy of sorafenib in post-LT era. METHODS: Consecutive patients with post-transplant HCC recurrence not eligible to resection or locoregional therapy were included. Patients receiving best supportive care (BSC) until 2007 were compared with those treated by sorafenib thereafter. RESULTS: Of a total of 65 patients, 20 patients received BSC and 45 received sorafenib. Clinical characteristics were similar between two groups except that sorafenib group received tacrolimus and mammalian target-of-rapamycin inhibitors more frequently than BSC group. Treatment with sorafenib conferred a survival advantage as compared with BSC for survival after recurrence (median, 14.2 vs. 6.8 months; P = 0.01). In multivariate analyses, high serum α-fetoprotein level, synchronous intrahepatic recurrence and distant metastasis at the time of recurrence, and BSC were independently associated with poorer survival after recurrence. Sorafenib treatment was associated with better survival after recurrence as compared with BSC (hazard ratio, 0.25; 95% confidence interval, 0.10–0.62; P = 0.002). In addition, sorafenib group showed tolerable toxicity in the post-transplant setting. CONCLUSION: Sorafenib may be beneficial in patients with post-transplant HCC recurrence.